406 Sentinel lymph node in cervical and endometrial cancer: review of the first 58 cases in a university setting. (13th November 2020) - Brañes, J; Jensen, R; Mergudich, T; Jara, A; García, K; Orlandini, E; Pertossi, E; Cuello, M; Majerson, D; Gejman, R
Abstract : Introduction: Lymphadenectomy is a common procedure in gynecologic oncology. Nonetheless, it is associated to important number of side effects. During the last decade there have been enormous efforts to develop different SLN techniques to reduce complications without affecting survival. Objective: Evaluate the experience of SLN technique in a university setting. Methods: Retrospective review of 58 cervical and endometrial cancers evaluated with SLN. Results: Forty-one of the patients presented with uterine cervical cancer and 17 endometrial cancer. The method used for detection of the SLN was patent blue dye only in 42 patients (72%), technetium 99 in 2 (3.5%), both techniques was used in 10 (17%) and ICG in 4 (%) cases. 40 (69%) patients had laparoscopy. At least one pelvic SLN was detected in 53 (91.4%) 7 patients. Bilateral detection was achieved in 39 (67.2%). Most of the SLN were identified next to external iliac vessels and the obturator fossa. In 97% of the 92 samples identified as SLN had at least one lymph node detected. The mean of lymph-node count was 1.8 (1–7). Patients with uterine cervical cancer had neither SLN nor non-SLN positive. Four patients with endometrial cancer (23.52%) had metastasis on SLN. There were no false negative SLN on those patients who underwent lymphadenectomy. There were no surgical complications derived from de SLN technique. Conclusion: SLN technique in cervical and endometrial cancer is technically feasible. Our results show that a good detection rate can be achieved for a proper diagnostic of lymph node status.